The Effects of Psychological Interventions on Symptoms and Psychology of Functional Dyspepsia: A Systematic Review and Meta-Analysis - Wei, Zhongcao; Xing, Xin; Tantai, Xinxing; Xiao, Cailan; Yang, Qian; Jiang, Xiaosa; Hao, Yujie; Liu, Na; Wang, Yan; Wang, Jinhai (Frontiers in Psychology, 2022)
Background: The effects of psychological interventions on symptoms and psychology of functional dyspepsia (FD) remain unclear. We aimed to comprehensively evaluate the effects of psychological interventions on symptoms and psychology of FD. Methods:We searched the PubMed, Cochrane Library, and Embase electronic databases for randomized controlled trials (RCTs) evaluating the role of psychological interventions in FD patients published before July 2021. Standardized mean differences (SMDs), risk ratios (RRs) and 95% confidence intervals (CIs) were calculated by a random effects model. Subgroup analyses and sensitivity analyses were also performed. Results: Fourteen RCTs with a total of 1434 FD patients were included. Compared with the control group, psychological interventions were significantly more likely to symptom improvement [RR = 1.74, 95% CI (1.12, 2.72), p = 0.01], relieve gastrointestinal symptoms scores at follow up [SMD = - 1.06, 95% CI (- 1.55, - 0.57), p < 0.0001], relieve gastrointestinal symptoms scores at end of treatment [SMD = - 0.98, 95% CI (- 1.29 - 0.67), p < 0.001], decrease anxiety [SMD = - 0.8, 95% CI ( - 1.38, -0.22), p = 0.006] and depression levels [SMD = - 1.11, 95% CI (- 1.62, - 0.61), p < 0.001]. The results of the subgroup analysis showed that psychotherapy was more likely to symptom improvement, relieve gastrointestinal symptoms scores and decreased depression levels compared to the control. Conclusions: Psychological interventions may be effective in alleviating the symptoms and psychology of FD, but the effect appears to be limited to psychotherapy with fewer trials for other psychological interventions. More data from high-quality RCTs are needed to confirm their use in the treatment of FD.